Identification of a functional allene oxide synthase-lipoxygenase fusion protein in the soft coral Gersemia fruticosa suggests the generality of this pathway in octocorals - Lõhelaid, Helike; Järving, Reet; Valmsen, Karin; Varvas, Külliki; Kreen, Malle; Järving, Ivar; Samel, Nigulas (Biochimica et biophysica acta, 2008)
The conversion of fatty acid hydroperoxides to allene epoxides is catalysed by a cytochrome P450 in plants. In contrast, in the coral Plexaura homomalla, a catalase-related hemoprotein fused to the lipoxygenase (LOX) was found to function as an allene oxide synthase. This work reports the homology-based RT-PCR cloning and functional expression of a Gersemia fruticosa analogue of the allene oxide synthase-lipoxygenase (AOS-LOX) fusion protein. The G. fruticosa mRNA codes for a protein with 84% sequence identity to the P. homomalla AOS-LOX. Our data indicate that the AOS-LOX fusion protein pathway is used by another coral and P. homomalla represents no exception.